A mobile based environmental education for primary schoolchildren in Malaysia - Savita, K.S. (IEEE Computer Society, 2017)
Environmental sustainability is the direction where every nation including Malaysia is heading towards. The ever rising environmental issues on industrial pollution and daily life activities affecting our rivers, oceans, extinction of certain plant species and fish species as well deforestation had produced serious consequences that bring negative implication to the world. The Malaysian government has taken steps to overcome these problems through the implementation of 11th Malaysia Plan where one of the main key areas is creating green environment and sustainability nation. In order to realize this focus, Malaysian government needs the cooperation of the society. An environmental caring society could only be established if this habit is cultivated at young age. One obvious method to nurture environmental friendly practices is through education for primary school children. A local school were targeted and studied in terms of assessing the current syllabus as well as to ensure the limitations of available tool to guide the teachers in educating the children. In this study, a solution in the form of mobile based application incorporating standard four syllabuses on environmental education topic has been proposed to overcome the limitations. The prototype was tested among primary school children and received positive feedbacks indicating that the proposed solution is a long term remedy to protect the environment from further vandalism and to recover the nature from current pollution. © 2017 IEEE.